Fashion and the environment a trend or a way of business? - Regala, Anna Rosario Castaneda
The current environmental involvement of the fashion and garment companies has been perceived by most people to be just a passing trend. However, the results from his research proved otherwise. It was becoming a way of business. Ten of the fashion and garment companies who have shown environmental concerns were made as subjects. Research Questionnaires were given to determine: development of environmental involvement; manifestations and degree of environmental involvement in the different areas (Advertising, Visual Merchandising, Clothing Design, Product Improvement & Packaging Modification, Company & Factory Operations & Procedures, and Participation in Environmental Activities and Projects); problems they have encountered their products acceptance and their future plans regarding their environmental involvement. Degrees of of environmental involvement were statistically treated with the use of the t-test and resulted to an average degree of environmental involvement. Results revealed an average overall degree of environmental involvement (26% to 50%), a positive product acceptance, more than two years of involvement and continuance of environmental efforts, indicating that it was becoming a way of business. However, environmental involvement in certain areas such as Product Improvement & Packaging Modification, Company & Factory Operations & Procedures and Advertising; and for environmental concerns such as Air & Noise Pollution Control and Natural Resources Conservation, specifically, Flood Control & Natural Calamities, Energy Development, Conservation & Utilization of Surface Ground Water and Mineral Resources were less than average and should be increased. Further studies on specific environmental concerns and efforts of fashion and garment companies and modifications on research design were recommended.